2018
DOI: 10.1021/acsphotonics.7b01496
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Photoluminescence of CH3NH3PbI3 Deposits on Nonplanar, Strongly Curved Substrates

Abstract: Organic−inorganic metal halide perovskites have recently attracted increasing attention as highly efficient light harvesting materials for photovoltaic applications. The solution processability of these materials is one of their major advantages on the route toward fabrication of low-cost solar cells and optoelectronic devices. However, the precise control of crystallization and morphology of organometallic perovskites deposited from solutions, considered crucial for enhancing the final photovoltaic performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…It is noteworthy to mention that thin-film deposits of MAPbI 3 coated by single-step solution casting from neat DMF solutions very often appear to show microwire-or fibre-like surface morphology [51]. We also have previously reported similar microwire-like morphology and practically identical luminescence characteristics for single-step solution cast deposits of MAPbI 3 on various types of both curved and flat substrates (microwires with sizes of ∼8 μm in diameter and up to ∼150 μm in length were observed for small substrates' curvatures or flat surfaces) [52]. Therefore, one can conclude that the presence of blue-TiO 2 NWs does not significantly modify nucleation and crystal growth of MAPbI 3 microwires during deposition of the MAPbI 3 /blue-TiO 2 NWs nanohybrid from stoichiometric solutions of MAPbI 3 in DMF (for more details see section 2 and supplementary material, available online atstacks.iop.org/JPPHOTON/2/014007/mmedia).…”
Section: Quantification Of the Charge Transfer At The Mapbi 3 /Blue-tsupporting
confidence: 62%
“…It is noteworthy to mention that thin-film deposits of MAPbI 3 coated by single-step solution casting from neat DMF solutions very often appear to show microwire-or fibre-like surface morphology [51]. We also have previously reported similar microwire-like morphology and practically identical luminescence characteristics for single-step solution cast deposits of MAPbI 3 on various types of both curved and flat substrates (microwires with sizes of ∼8 μm in diameter and up to ∼150 μm in length were observed for small substrates' curvatures or flat surfaces) [52]. Therefore, one can conclude that the presence of blue-TiO 2 NWs does not significantly modify nucleation and crystal growth of MAPbI 3 microwires during deposition of the MAPbI 3 /blue-TiO 2 NWs nanohybrid from stoichiometric solutions of MAPbI 3 in DMF (for more details see section 2 and supplementary material, available online atstacks.iop.org/JPPHOTON/2/014007/mmedia).…”
Section: Quantification Of the Charge Transfer At The Mapbi 3 /Blue-tsupporting
confidence: 62%
“…Many research groups dedicated to investigating the relationship between those two, and it was reported that a structured substrate can facilitate the growth of compact and continuous perovskite thin film. [20][21][22][23][24][25] Here in our research, we proposed a two-fluid spray coating technique, combined with volatile ink solution and preheated substrate ( Figure S1, Supporting Information), to fabricate a structured ETL composed of LT-TiO 2 NCs.…”
Section: Lt-tio 2 Film Depositionmentioning
confidence: 99%
“…It has been mentioned that the mesostructured ETL can facilitate the extraction of electron. [20][21][22][23][24][25] Besides, the texture of substrate can significantly influence the crystallization process of perovskite layer during deposition. S. Liu group has declared that perovskite layer with increased crystallinity and surface coverage can be achieved via controlling the wettability between perovskite droplet and the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have attempted to prepare MAPbI 3 nanocrystals with different morphologies, including zero-dimension (0D) nanodots, one-dimensional (1D) nanowires, nanorods, and nanobelts, 2D nanoplates, and three-dimensional (3D) nanocubes, by different preparation methods, including the dissolution-recrystallization method [20], conventional deposition method [21], and solution phase method [22]. However, the morphology of the prepared MAPbI 3 nanocrystals are not uniform, with the coexistence of nanowires, nanorods, nanoplates, and nanobelts in the sample, which may reduce PL intensity and weaken light absorption, which will be detrimental to their application in nanodevices [23].…”
Section: Introductionmentioning
confidence: 99%